TERT promoter mutations in solitary fibrous tumour. Issue 5 (19th September 2018) - Demicco, Elizabeth G; Wani, Khalida; Ingram, Davis; Wagner, Michael; Maki, Robert G; Rizzo, Anthony; Meeker, Alan; Lazar, Alexander J; Wang, Wei‐Lien
Abstract : Aims: TERT promoter mutations have been reported in 22% of solitary fibrous tumours (SFT) and have been associated with poor outcomes. We performed testing for TERT hot‐spot mutations in a large series of SFT in order to confirm this finding and explore clinicopathological correlates of mutation status. Methods and results: PCR for TERT hot‐spot mutations C250T and C228T was performed on DNA extracted from 216 SFT and mutation status correlated with clinicopathological factors, including predicted risk for metastasis using a previously published model. Testing was successful in 189 tumours from 172 patients, and mutations were present in 29%. The presence of TERT promoter mutation was associated with larger primary tumour size, necrosis and older patient age. TERT promoter mutations were most common in high‐risk tumours (nine of 20, 45%), and were present in 11 of 26 (42%) moderate‐risk tumours and 14 of 67 (21%) low‐risk tumours ( P  = 0.004). Overall, TERT mutations were associated with shorter time to first metastasis ( P  = 0.04), but had no impact on overall survival. TERT promoter mutation status was found not to provide additional prognostic information in low‐ and high‐risk SFT, but did identify a group of patients with intermediate risk SFT who had an increased risk of metastasis. Conclusions: TERT promoter mutations were more frequent in SFT with higher risk of metastasis, but TERT promoter mutation status was not a reliable predictor of clinical outcome by itself. However, mutations in the TERT promoter may be useful in further stratifying patients with intermediate risk tumours.